Developing a Classroom Climate Scale for Students in Arabic Language Departments (Journal Of Educational and Psychological Researches, 2024)
The current research aims to develop a scale of the classroom climate among students of Arabic language departments and to measure the level of their classroom climate. The researcher used the descriptive approach. The research sample comprised 400  male and female students who were randomly chosen from the research community. The researcher developed the classroom climate scale, which included (16) items in its final form distributed into (3) domains: the physical environment, the social environment, and the moral environment, with three alternatives for the physical environment: (well available, poorly available, not available) and three alternatives for the social and moral environment: sometimes yes, no. After applying the scale, the results showed that students in the Arabic language departments have a high level of classroom interaction. No differences appeared between them in classroom interaction. Based on these results, the research came up with several recommendations, including Improving the classroom climate by providing an atmosphere of reassurance and trust that encourages students to interact and participate in a way that contributes to creating positive relationships between them and makes them accept each other, in addition to several suggestions included: Conducting a study to find out the classroom climate and its relationship to classroom Learning patterns among university students